PEMBAYARAN KAPITASI BERBASIS KINERJA PADA FASILITAS KESEHATAN TINGKAT PERTAMA (FKTP) KOTA MALANG - Anggi Ardhiasti; Eko Rahman Setiawan (Jurnal Pendidikan Kesehatan, 2021)
JKN applies the performance baxed capitation payment or called KBKP or Kapitasi Berbasis Komitmen Pelayanan in Primary health Care or FKTP, with 3 indicators, namely Contact Rate, Non Specialistic Referral Ratio, and Routine Visiting Prolanis Participant Ratio. The preliminary study for January until July 2019, the KBKP of Malang City is still low. The purpose of this research is to explore the application of KBKP from the point of view of policy implementation theory.The research method is a mix method with informants 8 FKTP, Malang Health Office, and BPJS Kesehatan KC Malang.The results showed that no one FKTP had received full capitation in 2019. The implementation of the socialization and evaluation policy has been running. Constraints in the availability of resources related to the operation of the p care application. The implementation of budgeting is adequate both from capitation, BOK and BLUD. The FKTP heads play a role in encouraging the fulfillment of the KBKP by motivating them to achieve targets, but there are FKTP heads who do not care much about the implementation of the KBKP. The Health Office has not implemented a reward and punishment policy in encouraging efforts to fulfill the KBKP. The fulfillment of the 2019 KBK at the FKTP in Malang City is still not optimal, competence in the FKTP is still an obstacle, and the Health Office has not implemented incentive and disincentive policies in fulfilling the KBKP indicators.